DO WE NEED A WEB-BASED ANALYSIS FOR VILLAGE FUND ACCOUNTABILITY? LESSONS LEARNED FROM DETOSUKO BARAT - Aprina Nugrahesthy; Anis Chariri (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study aims to evaluate the accountability practices of village financial management based on the official village website. West Detusoko, one of the anti-corruption pilot villages in 2022, was selected as the research object. This study adopts case study research approach. We collect data by observing the official village website, evaluating suitability with the accountability criteria, and then conducting in-depth interviews with informants to draw an overview of the accountability representation of village financial management through the official village website. The finding shows that the official website of West Detusoko falls into the less accountable category. The official website of West Detusoko has run actively because some actors behind the scenes have an interest in creating an impression on the village to the audiences accessing the official village website. The lessons learned from the case is the need of stakeholder awareness for providing the village with necessary resources in the implementation of website-based accountability. The website as a form of social interaction is expected to be a means of communication between all stakeholders, one of which is in representing the accountability of village financial management.